The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnagi.2021.679837
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Hypothesis on Dementia: Inflammation, Small Vessel Disease, and Hypoperfusion Is the Sequence That Links All Harmful Lifestyles to Cognitive Impairment

Abstract: There is growing consensus that certain lifestyles can contribute to cognitive impairment and dementia, but the physiological steps that link a harmful lifestyle to its negative impact are not always evident. It is also unclear whether all lifestyles that contribute to dementia do so through the same intermediary steps. This article will focus on three lifestyles known to be risk factors for dementia, namely obesity, sedentary behavior, and insufficient sleep, and offer a unifying hypothesis proposing that lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 128 publications
1
15
1
Order By: Relevance
“…The multifaceted physiological consequences of depression described here conform to the already outlined pattern for other recognized risks for dementia such as obesity, sedentary lifestyle and inadequate sleep ( Hakim, 2021 ). The major difference between depression and the other cognitive risk factors is the possibility of offering various therapeutic modalities to the affected individuals.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The multifaceted physiological consequences of depression described here conform to the already outlined pattern for other recognized risks for dementia such as obesity, sedentary lifestyle and inadequate sleep ( Hakim, 2021 ). The major difference between depression and the other cognitive risk factors is the possibility of offering various therapeutic modalities to the affected individuals.…”
Section: Discussionsupporting
confidence: 76%
“…The recognition that certain risk factors increase the risk for dementia provides the possibility of reducing this burden by intensifying efforts to reduce and control the risk factors. In a recent article ( Hakim, 2021 ), a hypothesis was presented that a sequence of physiological events links dementia risk factors to their cognitive outcomes. It was proposed that in the presence of a risk factor, the sequence that leads to dementia is triggered by inflammation which leads to cerebral small vessel disease.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle-related diseases, including diabetes mellitus, play a role in the development of dementia by activating chronic inflammatory processes associated with oxidative stress. These changes lead to small vessel diseases, resulting in a reduction in CBF ( 37 39 ). In addition, lifestyle-related diseases can also result in arteriosclerosis of large vessels, leading to a decrease in CBF.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding DWML pathogenesis, decreased cerebral blood flow or a blood–brain barrier disruption induced by endothelial damage of cerebral deep small arteries have been reported 33–35 . Experimental studies have revealed that chronic cerebral hypoperfusion causes myelin sheath damage and neuronal death, 36,37 while endothelial cells of deep small arteries have been reported to be injured by chronic inflammatory response caused by hypertension, diabetes mellitus, dyslipidemia, smoking, and chronic kidney disease 38 . With respect to our study, no difference was observed in the incidence of hypertension and diabetes mellitus between the Cons[+] and Cons[−] groups, and the incidence of hyperlipidemia was rather lower in the Cons[+] group.…”
Section: Discussionmentioning
confidence: 99%